2005
DOI: 10.1126/science.1110837
|View full text |Cite
|
Sign up to set email alerts
|

Anchorless Prion Protein Results in Infectious Amyloid Disease Without Clinical Scrapie

Abstract: In prion and Alzheimer's diseases, the roles played by amyloid versus nonamyloid deposits in brain damage remain unresolved. In scrapie-infected transgenic mice expressing prion protein (PrP) lacking the glycosylphosphatidylinositol (GPI) membrane anchor, abnormal protease-resistant PrPres was deposited as amyloid plaques, rather than the usual nonamyloid form of PrPres. Although PrPres amyloid plaques induced brain damage reminiscent of Alzheimer's disease, clinical manifestations were minimal. In contrast, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
613
6
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 588 publications
(671 citation statements)
references
References 37 publications
48
613
6
4
Order By: Relevance
“…This notion was confirmed by neuron-specific ablation of Prnp (Mallucci et al, 2003) and in mice expressing anchorless PrP, which is converted into a protease-resistant isoform and forms amyloid plaques yet causes minimal neuronal damage (Chesebro et al, 2005).…”
mentioning
confidence: 56%
“…This notion was confirmed by neuron-specific ablation of Prnp (Mallucci et al, 2003) and in mice expressing anchorless PrP, which is converted into a protease-resistant isoform and forms amyloid plaques yet causes minimal neuronal damage (Chesebro et al, 2005).…”
mentioning
confidence: 56%
“…However, recent studies have begun to question this view. As one striking example in mice, deletion of the GPI anchor of the prion protein PrP leads to massive extracellular amyloid plaque formation in mice injected with infective scrapie, but causes no overt clinical manifestations of scrapie (32). Furthermore, it has been suggested that neurodegenerative diseases are caused by the ability of very different proteins to adopt common toxic nonamyloid conformers such as protofibrils or soluble oligomers (3,5).…”
Section: Discussionmentioning
confidence: 99%
“…Case in point, when GPI-anchorless PrP was expressed together with WT PrP, it accelerated scrapie disease and resulted in increased deposits of both amyloid and nonamyloid proteinase K-resistant PrP (32). Similarly, in yeast, the toxicity of Huntington exon 1 depends on the [RNQ ϩ ] prion state (16,22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PrP sc does not infect neurospheres derived from PrP c knockout mice in vitro (Giri et al, 2006), and Prnp null mice are re-sensitized to prion infection even when several aminotruncated PrP c constructs are expressed (Aguzzi and Heikenwalder, 2006;Aguzzi and Polymenidou, 2004;Fischer et al, 1996;Flechsig et al, 2000). Regarding the presence of PrP c for prion transmission, GPI-anchoring has been proposed as a key factor in scrapie infection; in fact, mice lacking GPI fail to reproduce clinical scrapie, although amyloid deposition is present (Chesebro et al, 2005). These studies demonstrate that the presence of PrP c is indispensable for prion pathologies and that the interaction of this protein with the plasma membrane contributes to neurodegeneration.…”
Section: Prp C Expression and Prion Pathologymentioning
confidence: 99%